Use of theatrical games as a pedagogical tool in medical humanities (Research, Society and Development, 2022)
The present study aims to describe a set of activities carried out within the Medical Humanities axis, using the theatrical game as a pedagogical tool for the construction of knowledge within the undergraduate medical course. Methodology: This work reports the experience built over two years, with the use of theatrical games of professional practice in the teaching-learning process of the undergraduate course in Medicine at Universidade CEUMA, Campus Imperatriz, Maranhão. Its pedagogical framework is based on the constructivist approach to learning and on the theoretical framework of Viola Spolin. The present study starts from the premise that learning is not a mere reproduction of reality, however, it is a construction based on the personal representation of reality and its contents. The results were described according to the competences and abilities recommended for the medical student, according to the National Curriculum Guidelines for graduation in Medicine: Health care; Decision-making; Communication; Leadership; Administration and management; and Permanent Education. This pedagogical strategy proved to be a powerful instrument for the development of skills and competences in the medical field.